Silicon carbide / red phosphorus composite material for SERS detection and preparation method thereof

By preparing the potato tower-shaped silicon carbide/red phosphorus composite as the SERS substrate, the problem of insufficient detection performance of SERS substrate materials in the prior art is solved, high sensitivity and good stability are achieved, and the detection effect of methylene blue molecules is significantly improved.

CN115236061BActive Publication Date: 2025-04-18NINGBO UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211007978.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-22
Publication Date
2025-04-18
Estimated Expiration
2042-08-22

AI Technical Summary

Technical Problem

The prior art is difficult to prepare SERS substrate materials with excellent detection performance, especially in terms of sensitivity, uniformity, stability and reproducibility.

Method used

A composite material with a high specific surface area and matching energy band structure is prepared by uniformly adhering the red phosphorus to the surface of the potato tower-shaped silicon carbide, and a composite substrate is made using different molar ratios of silicon carbide and red phosphorus. A composite material with a high specific surface area and matching energy band structure is prepared through specific preparation steps such as ultrasonic cleaning, ultraviolet irradiation and calcination.

Benefits of technology

The high sensitivity, good biocompatibility and environmental stability of SERS detection are achieved, the chemical enhancement effect between the substrate and the detection molecule is improved, and the detection sensitivity of methylene blue molecules is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115236061B_ABST
    Figure CN115236061B_ABST
Patent Text Reader

Abstract

The present invention relates to a silicon carbide / red phosphorus composite material for SERS detection and a preparation method thereof. The present invention discloses for the first time a silicon carbide / red phosphorus composite material that can be used for SERS detection to realize the detection of methylene blue molecules. The material consists of two parts: potato-shaped silicon carbide and red phosphorus. The silicon carbide / red phosphorus composite substrate is prepared by mixing silicon carbide and red phosphorus in different molar ratios. The advantage is that the potato-shaped silicon carbide surface has a large specific surface area, which is conducive to obtaining a composite with red phosphorus material, greatly enhancing the Raman signal of the adsorbed molecules. At the same time, the two materials, silicon carbide and red phosphorus, have matching energy band structures, which can improve the ability of chemical enhancement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the fields of material engineering and nanotechnology, and in particular to a silicon carbide / red phosphorus composite material that can be used for SERS detection and a preparation method thereof. Background Art

[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Surface enhanced Raman spectroscopy is a powerful vibrational spectroscopy technique that can perform rapid and non-destructive analysis based on the unique molecular fingerprint characteristics of the analyte. Due to the strong dependence of Raman signals on surface enhanced Raman spectroscopy (SERS) substrates, people are committed to preparing suitable SERS substrates to meet the basic analytical requirements of sensitivity, uniformity, stability and reproducibility. In recent years, due to its ultra-high detection sensitivity at the single-molecule level, simple operation procedures and intuitive and visual detection results, this technology has been widely used in biochemical molecular detection under various conditions. To achieve its excellent detection performance, the preparation of SERS-active substrate materials is critical. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for preparing a potato-shaped silicon carbide / red phosphorus composite material that can be used for SERS detection.

[0005] In order to achieve the above object, the technical solution of the present invention is as follows:

[0006] In a first aspect, the present invention provides a potato-shaped silicon carbide / red phosphorus composite material for SERS detection, the material is composed of potato-shaped silicon carbide and red phosphorus, and the red phosphorus is uniformly attached to the surface of the potato-shaped silicon carbide. The silicon carbide / red phosphorus composite substrate is prepared by mixing silicon carbide and red phosphorus in different molar ratios.

[0007] In a second aspect, the present invention provides a method for preparing a potato-shaped silicon carbide / red phosphorus composite material that can be used for SERS detection, comprising the following steps:

[0008] (1) dissolving polycarbosilane and divinylbenzene in an organic solvent, reacting under the catalysis of a catalyst to obtain a polycarbosilane gel, drying and heat-treating to obtain a silicon carbide / carbon precursor aerogel, mixing the silicon carbide / carbon precursor aerogel, rice husk charcoal and silicon, and calcining under oxygen-free argon protection conditions to obtain a silicon carbide aerogel;

[0009] (2) ultrasonically cleaning the silicon carbide aerogel, immersing it in a hydrofluoric acid solution, and ultrasonically dispersing it under ultraviolet light; standing it, pouring out the supernatant, and the remaining solution is solution A; then adding solution A to deionized water, and then subjecting it to ultraviolet ultrasonic dispersion treatment and separation; repeating the above steps several times, and then centrifuging solution A, and then dispersing it into deionized water, and then centrifuging it, and repeating the above operation until the pH of the solution is 7, thereby obtaining silicon carbide nanowires;

[0010] (3) mixing the silicon carbide nanowires and red phosphorus, placing them in a muffle furnace for heating, and taking them out after the heating is completed, thereby obtaining a silicon carbide / red phosphorus composite material.

[0011] Furthermore, in step (1), the catalytic reaction is carried out under the conditions of 70 to 90° C. in the absence of oxygen for 4 to 8 hours.

[0012] Furthermore, the molar ratio of Si-H in polycarbosilane to CH2=CH- in divinylbenzene is 5-20.

[0013] Furthermore, in step (1), the heat treatment refers to keeping the temperature at 1000-2000° C. for 1-6 hours in the absence of oxygen.

[0014] Furthermore, the molar ratio of the silicon carbide / carbon precursor aerogel, rice husk charcoal and silicon powder is 1:2:2.

[0015] Furthermore, in step (1), calcination is performed at 1000-1800° C. for 0.5-5 h.

[0016] Furthermore, the ultrasonic cleaning is specifically carried out in acetone, anhydrous ethanol, and deionized water for 10 to 20 minutes respectively.

[0017] Furthermore, the mass percentage concentration of the hydrofluoric acid solution is 98%.

[0018] Furthermore, the mixture is ultrasonically dispersed under ultraviolet light for 0.5 to 3 hours.

[0019] Furthermore, the standing time is 30 to 500 minutes.

[0020] Furthermore, the silicon carbide treatment process is carried out in an ultrasonic bath environment, and the parameters of the ultrasonic bath are: ultrasonic power of 150W, solution temperature of 30-50°C, ultraviolet light parameters of wavelength of 365nm, and light power of 5-10W.

[0021] Furthermore, the molar ratio of silicon carbide nanowires to red phosphorus is 1 to 3.5:1.

[0022] Furthermore, the heating conditions in the muffle furnace are: a heating rate of 3 to 10° C. per minute, a heating temperature of 800 to 1000° C., and a holding time of 60 to 600 min.

[0023] In a third aspect, the present invention provides an application of the silicon carbide / red phosphorus composite material as a SERS substrate; the application can be for the detection of methylene blue molecules.

[0024] As a SERS substrate, the silicon carbide / red phosphorus composite material has good biocompatibility and environmental stability, as well as a high chemical enhancement effect. At the same time, the introduction of the potato-shaped substrate can further enhance the chemical enhancement effect between the substrate and the detection molecule, which is conducive to improving the detection sensitivity of the SERS technology. In addition, the SERS technology based on the silicon carbide / red phosphorus composite material can achieve a higher sensitivity diagnosis for the detection of methylene blue molecules.

[0025] Compared with the prior art, the advantages of the present invention are: the present invention discloses for the first time a silicon carbide / red phosphorus composite material that can be used for SERS detection to realize the detection of methylene blue molecules, and the material is composed of two parts: potato-shaped silicon carbide and red phosphorus. Among them, a silicon carbide / red phosphorus composite substrate is prepared by mixing silicon carbide and red phosphorus in different molar ratios. Its advantage is that the potato-shaped silicon carbide surface has a large specific surface area, which is conducive to obtaining a composite with red phosphorus material, greatly enhancing the Raman signal of the adsorbed molecules. At the same time, the two materials, silicon carbide and red phosphorus, have matching energy band structures, which can improve the ability of chemical enhancement. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0027] Figure 1 This is a scanning electron microscope photograph of the potato-shaped silicon carbide prepared in Example 1 of the present invention;

[0028] Figure 2 This is a scanning electron microscope photograph of the silicon carbide / red phosphorus composite material prepared in Example 1 of the present invention;

[0029] Figure 3 XRD detection of the silicon carbide / red phosphorus composite material prepared in Example 1 of the present invention;

[0030] Figure 4 The SERS detection of methylene blue molecules by the silicon carbide / red phosphorus composite material prepared in Example 1 of the present invention;

[0031] Figure 5 This is a scanning electron microscope photograph of the silicon carbide / red phosphorus composite material prepared in Example 2 of the present invention;

[0032] Figure 6The SERS detection of methylene blue molecules by the silicon carbide / red phosphorus composite material prepared in Example 2 of the present invention;

[0033] Figure 7 This is a scanning electron microscope photograph of the silicon carbide / red phosphorus composite material prepared in Example 3 of the present invention;

[0034] Figure 8 This is the SERS detection of methylene blue molecules by the silicon carbide / red phosphorus composite material prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0035] It should be noted that the following detailed descriptions are all illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0036] The present invention is further described in detail below with reference to the accompanying drawings.

[0037] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art, and the raw materials used are all commercially available products.

[0038] Example 1

[0039] A method for preparing a silicon carbide / red phosphorus composite material comprises the following steps:

[0040] (1) Preparation of silicon carbide aerogel

[0041] Polycarbosilane and divinylbenzene were dissolved in an organic solvent, and the reaction was catalyzed by Karstedt catalyst at 90°C in the absence of oxygen for 4 hours to obtain polycarbosilane gel, which was then dried to obtain polycarbosilane aerogel. The polycarbosilane aerogel was then heat-treated to obtain silicon carbide / carbon precursor aerogel. Finally, it was mixed with rice husk charcoal and silicon powder in a molar ratio and calcined at 1800°C for 0.5h under oxygen-free argon protection to obtain silicon carbide aerogel.

[0042] (2) Fabrication of potato-shaped silicon carbide nanowires

[0043] Weigh 5g of the prepared silicon carbide aerogel, ultrasonically clean it in acetone, anhydrous ethanol, and deionized water for 10 minutes, then immerse it in 50mL of 98% hydrofluoric acid solution, and ultrasonically disperse it under ultraviolet light for 0.5h. After the ultrasound is over, let it stand for 30 minutes, pour out the supernatant (90mL), and the remaining solution becomes solution A. Then add a certain amount of deionized water (90mL) to solution A, and then disperse and separate it by ultraviolet light ultrasonic dispersion. After repeating the above steps 5 times, put solution A into a centrifuge tube and centrifuge to obtain silicon carbide nanowires, which are then dispersed in deionized water and centrifuged again. Repeat the above operation until the pH of the solution is 7, and obtain a single-crystal potato-shaped silicon carbide without impurities, monodispersed, 3C phase, density of 3.21g / cc, uniform size distribution, diameter of 50nm, and length of 10μm, which is dried and stored for use. The above silicon carbide treatment process is carried out in an ultrasonic bath environment, and the parameters of the ultrasonic bath are: ultrasonic power of 150W, solution temperature of 30°C, ultraviolet light parameters of wavelength of 365nm, and light power of 5W.

[0044] (3) Preparation of silicon carbide / red phosphorus composites

[0045] 0.01 mol of the treated silicon carbide nanowires and 0.01 mol of red phosphorus were mixed evenly and added to a platinum tube for sealing. The sealed platinum tube was placed in a muffle furnace for heating at a heating rate of 3°C per minute, a heating temperature of 800°C, and a holding time of 60 minutes. After the heating was completed, the sample was naturally cooled to room temperature in the furnace and then taken out to obtain a silicon carbide / red phosphorus composite material.

[0046] Figure 1 The transmission electron microscope photo of the silicon carbide material prepared in this embodiment is shown. Figure 1 It can be seen that the prepared silicon carbide has a potato tower-like structure.

[0047] Figure 2 The transmission electron microscope photo of the silicon carbide / red phosphorus composite material prepared in this example is shown. Figure 2 It can be seen that red phosphorus is evenly attached to the potato-shaped silicon carbide surface.

[0048] Figure 3 The XRD pattern of the silicon carbide / red phosphorus composite material prepared in this example is shown.

[0049] Figure 4 The SERS spectrum of methylene blue molecules detected by silicon carbide / red phosphorus composite material shows that the intensity at 1621 wavenumber is 7690, which is much higher than the Raman enhancement effect of using silicon carbide material alone (2690). This is mainly due to the chemical enhancement effect produced by the silicon carbide / red phosphorus composite material.

[0050] Example 2

[0051] A method for preparing a silicon carbide / red phosphorus composite material comprises the following steps:

[0052] (1) Preparation of silicon carbide aerogel

[0053] Polycarbosilane and divinylbenzene were dissolved in an organic solvent, and the reaction was catalyzed by Karstedt catalyst at 70°C in the absence of oxygen for 8 hours to obtain polycarbosilane gel, which was then dried to obtain polycarbosilane aerogel. The polycarbosilane aerogel was then heat-treated to obtain silicon carbide / carbon precursor aerogel, which was finally mixed with rice husk charcoal and silicon powder in a molar ratio and calcined at 1000°C for 5 hours under oxygen-free argon protection to obtain silicon carbide aerogel.

[0054] (2) Fabrication of potato-shaped silicon carbide nanowires

[0055] Weigh 5g of the prepared silicon carbide aerogel, ultrasonically clean it in acetone, anhydrous ethanol, and deionized water for 20min, then immerse it in 500mL of 98% hydrofluoric acid solution, and ultrasonically disperse it under ultraviolet light for 3h. After the ultrasound is over, let it stand for 500min, pour out the supernatant (450mL), and the remaining solution becomes solution A. Then add a certain amount of deionized water (450mL) to solution A, and then disperse and separate it by ultraviolet ultrasonic dispersion. After repeating the above steps 8 times, put solution A into a centrifuge tube and centrifuge to obtain silicon carbide nanowires, which are then dispersed in deionized water and centrifuged again. Repeat the above operation until the pH of the solution is 7, and obtain single-crystal potato-shaped silicon carbide that is free of impurities, monodispersed, has a crystal phase of 3C phase, a density of 3.21g / cc, and a uniform size distribution with a diameter of 50-300nm and a length of 10-100μm. After drying, store it for use. The above silicon carbide treatment process is carried out in an ultrasonic bath environment, and the parameters of the ultrasonic bath are: ultrasonic power of 150W, solution temperature of 50°C, ultraviolet light parameters of wavelength of 365nm, and light power of 10W.

[0056] (3) Preparation of silicon carbide / red phosphorus composites

[0057] 0.02 mol of the treated silicon carbide nanowires and 0.01 mol of red phosphorus were mixed evenly and added to a platinum tube for sealing. The sealed platinum tube was placed in a muffle furnace for heating at a heating rate of 10°C per minute, a heating temperature of 1000°C, and a holding time of 600 min. After the heating was completed, the sample was naturally cooled to room temperature with the furnace and then taken out to obtain a silicon carbide / red phosphorus composite material.

[0058] Figure 5 The transmission electron microscope photo of the silicon carbide / red phosphorus composite material prepared in this example is shown. Figure 5 It can be seen that red phosphorus is evenly attached to the potato-shaped silicon carbide surface.

[0059] Figure 6 The SERS spectrum of methylene blue molecules detected by silicon carbide / red phosphorus composite material shows that the intensity at 1621 wavenumber is 4494, which is much higher than the Raman enhancement effect of using a single silicon carbide material (2690). This is mainly due to the chemical enhancement effect produced by the silicon carbide / red phosphorus composite material.

[0060] Example 3

[0061] A method for preparing a silicon carbide / red phosphorus composite material comprises the following steps:

[0062] (1) Preparation of silicon carbide aerogel

[0063] Polycarbosilane and divinylbenzene were dissolved in an organic solvent, and the reaction was catalyzed by Karstedt catalyst at 90°C in an oxygen-free environment for 6 hours to obtain polycarbosilane gel, which was then dried to obtain polycarbosilane aerogel. The polycarbosilane aerogel was then heat-treated to obtain silicon carbide / carbon precursor aerogel, which was finally mixed with rice husk charcoal and silicon powder in a molar ratio and calcined at 1500°C for 2 hours under oxygen-free argon protection to obtain silicon carbide aerogel.

[0064] (2) Fabrication of potato-shaped silicon carbide nanowires

[0065] Weigh 5g of the prepared silicon carbide aerogel, ultrasonically clean it in acetone, anhydrous ethanol, and deionized water for 20min, then immerse it in 100mL of 98% hydrofluoric acid solution, and ultrasonically disperse it under ultraviolet light for 2h. After the ultrasound is over, let it stand for 60min, pour out the supernatant (100mL), and the remaining solution becomes solution A. Then add a certain amount of deionized water (200mL) to solution A, and then disperse and separate it by ultraviolet ultrasonic treatment. After repeating the above steps 7 times, put solution A into a centrifuge tube and centrifuge to obtain silicon carbide nanowires, which are then dispersed in deionized water and centrifuged again. Repeat the above operation until the pH of the solution is 7, and obtain single-crystal potato-shaped silicon carbide that is free of impurities, monodispersed, has a crystal phase of 3C phase, a density of 3.21g / cc, and a uniform size distribution with a diameter of 50-300nm and a length of 10-100μm. After drying, store it for use. The above silicon carbide treatment process is carried out in an ultrasonic bath environment, and the parameters of the ultrasonic bath are: ultrasonic power of 150W, solution temperature of 40°C, ultraviolet light parameters of wavelength of 365nm, and light power of 8W.

[0066] (3) Preparation of silicon carbide / red phosphorus composites

[0067] 0.035 mol of the treated silicon carbide nanowires and 0.01 mol of red phosphorus were mixed evenly and added to a platinum tube for sealing. The sealed platinum tube was placed in a muffle furnace for heating at a heating rate of 5°C per minute, a heating temperature of 900°C, and a holding time of 120 min. After the heating was completed, the sample was naturally cooled to room temperature in the furnace and then taken out to obtain a silicon carbide / red phosphorus composite material.

[0068] Figure 7 The transmission electron microscope photo of the silicon carbide / red phosphorus composite material prepared in this example is shown. Figure 7 It can be seen that red phosphorus is evenly attached to the potato-shaped silicon carbide surface.

[0069] Figure 8 The SERS spectrum of methylene blue molecules detected by using silicon carbide red phosphorus composite material shows that the intensity at 1621 wavenumber is 3913, which is much higher than the Raman enhancement effect of using a single silicon carbide material (2690). This is mainly due to the chemical enhancement effect produced by the silicon carbide / red phosphorus composite material.

[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A potato-shaped silicon carbide / red phosphorus composite material, characterized in that: The potato-tower-shaped silicon carbide / red phosphorus composite material consists of two parts: potato-tower-shaped silicon carbide and red phosphorus. The red phosphorus is uniformly attached to the surface of the potato-tower-shaped silicon carbide.

2. A method for preparing the potato-shaped silicon carbide / red phosphorus composite material as claimed in claim 1, characterized in that: The following steps are involved: (1) dissolving polycarbosilane and divinylbenzene in an organic solvent, reacting under the catalysis of a catalyst to obtain a polycarbosilane gel, drying and heat-treating to obtain a silicon carbide / carbon precursor aerogel, mixing the silicon carbide / carbon precursor aerogel, rice husk charcoal and silicon, and calcining under oxygen-free argon protection conditions to obtain a silicon carbide aerogel; (2) ultrasonically cleaning the silicon carbide aerogel, immersing it in a hydrofluoric acid solution, and ultrasonically dispersing it under ultraviolet light; Let it stand, pour out the supernatant, and the remaining solution is solution A; Then, solution A is added to deionized water, and then subjected to ultraviolet ultrasonic dispersion treatment and separation; the above steps are repeated several times, and solution A is centrifuged, and then dispersed into deionized water, and then subjected to centrifugation treatment, and the above operation is repeated until the pH value of the solution is 7, thereby obtaining silicon carbide nanowires; (3) mixing the silicon carbide nanowires and red phosphorus, placing them in a muffle furnace for heating, and taking them out after the heating is completed, thereby obtaining a silicon carbide / red phosphorus composite material.

3. The preparation method according to claim 2, characterized in that: In step (1), the catalytic reaction is carried out under the conditions of 70 to 90° C. and in the absence of oxygen for 4 to 8 hours.

4. The preparation method according to claim 2, characterized in that: The molar ratio of Si-H in polycarbosilane to CH2=CH- in divinylbenzene is 5 to 20; Or, in step (1), the heat treatment refers to keeping the temperature at 1000-2000° C. for 1-6 hours in the absence of oxygen; Alternatively, the molar ratio of the silicon carbide / carbon precursor aerogel, rice husk charcoal and silicon powder is 1:2:

2.

5. The preparation method according to claim 2, characterized in that: In step (1), calcination is performed at 1000-1800° C. for 0.5-5 h.

6. The preparation method according to claim 2, characterized in that: In step (2), ultrasonic cleaning is specifically performed in acetone, anhydrous ethanol, and deionized water for 10 to 20 minutes respectively; Or, the mass percentage concentration of the hydrofluoric acid solution is 98%.

7. The preparation method according to claim 2, characterized in that: Ultrasonic dispersion under ultraviolet light for 0.5 to 3 hours; Or, the standing time is 30 to 500 minutes.

8. The preparation method according to claim 2, characterized in that: The silicon carbide treatment process is carried out in an ultrasonic bath environment, and the parameters of the ultrasonic bath are: ultrasonic power is 150W, solution temperature is 30-50°C, ultraviolet light parameters are wavelength 365nm, and light power is 5-10W.

9. The preparation method according to claim 2, characterized in that: The molar ratio of silicon carbide nanowires to red phosphorus is 1 to 3.5:1; Alternatively, the heating conditions in the muffle furnace are: a heating rate of 3 to 10° C. per minute, a heating temperature of 800 to 1000° C., and a holding time of 60 to 600 min.

10. Use of the potato-tower-shaped silicon carbide / red phosphorus composite material according to claim 1 or the potato-tower-shaped silicon carbide / red phosphorus composite material prepared by the preparation method according to any one of claims 2 to 9 as a SERS substrate.

11. The use according to claim 10, wherein the use is specifically for detecting methylene blue molecules.